CONTRACTUAL JUSTICE IN ISLAMIC LAW: A CRITICAL EXAMINATION OF EQUITY AND RISK ALLOCATION - Ahmed Al Mohannadi; Mariam Al Thani; Tim Bauer (Yayasan Adra Karima Hubbi, 2026)
Contractual justice is a foundational principle in Islamic law, emphasizing equity, fairness, and balanced risk allocation in economic transactions. Contemporary Islamic finance, however, operates within complex market environments that often prioritize formal compliance and financial efficiency, raising concerns about whether contractual practices genuinely reflect these normative ideals. This study aims to critically examine the relationship between equity and risk allocation in Islamic financial contracts and to assess the extent to which current practices align with foundational Shariah principles. A qualitative normative–juridical research design is employed through systematic analysis of 90 legal documents, including classical jurisprudential texts, fatwas, and regulatory frameworks across multiple jurisdictions. Analytical matrices and thematic coding are used to identify patterns of contractual structuring, risk distribution, and normative alignment. The findings reveal a divergence between equity-centered risk-sharing models and dominant risk-transfer structures, with compliance-oriented frameworks mediating between the two. Market pressures and institutional constraints significantly influence contractual design, often leading to reduced emphasis on substantive justice. The study concludes that contractual justice in Islamic law must be reconceptualized as a dynamic and context-dependent construct, requiring integrative governance approaches that align legal form with ethical substance.